Strengthening Financial Literacy to Raise Aware of Will Financial Planning and Management in Youth - Andy Wijaya; Julyanthry Julyanthry; Ruth Tridianty Sianipar; Onita Sari Sinaga; Sisca Sisca; Erbin Chandra (LPPM UIKA Bogor, 2023)
The implementation of community service activities with the theme Strengthening Financial Literacy to Increase Awareness of Financial Planning and Management among Young People aims to make the younger generation and especially young people of the Samiddha Bhagya Temple Pematang Siantar City who as members of the community have better financial literacy knowledge. An understanding of financial literacy is expected to increase high awareness of the importance of making financial planning and implementing effective and efficient financial management. The method used in carrying out this activity is through face-to-face lectures and discussions. The sequence of this activity begins with an opening, and presentation of material, and continues with discussion. Participants were very appreciative of this activity because it provided an understanding of the importance of financial planning and financial management for future financial security.